Do CMIP5 models reproduce observed low-frequency North Atlantic jet variability? - Woollings, T; Bracegirdle, T; Lu, H; Eade, R (John Wiley & Sons, Inc., 2018)
The magnitude of observed multi-decadal variations in the North Atlantic Oscillation (NAO) is at the upper end of the range simulated by climate models and a clear explanation for this remains elusive. Recent research shows that observed multi-decadal NAO variability is more strongly associated with North Atlantic (NA) jet strength than latitude, thus motivating a comprehensive comparison of NA jet and NAO variability across the CMIP5 models. Our results show that the observed peak in multi-decadal jet strength variability is even more unusual than NAO variability when compared to the model-simulated range across 133 historical CMIP5 simulations. Some CMIP5 models appear capable of reproducing the observed low-frequency peak in jet strength, but there are too few simulations of each model to clearly identify which. It is also found that an observed strong multi-decadal correlation between jet strength and NAO since the mid-19th century may be specific to this period.